Immigrattion: fears to cultural invasion - Rodríguez Kauth, Angel (Nómadas. Critical Journal of Social and Juridical Science, 2011)
It is a fact that the people of certain countries -especially the "central" ones- reject immigratoty processes. This text is about the fear to "cultural invasion", i.e. the fear that strangers can damage local cultural expressions. The article summarises basically the fears having to do with religion and language and it also discusses the function of art in the formation of xenophobic attitudes.